Comparative study on the effect of single coil and multi coil magnetorheological damper through finite element analysis. (December 2020) - Kariganaur, Ashok Kumar; Kumar, Hemantha; Mahalingam, Arun
Abstract: Magnetorheological damper is vibration reducing system in which the magnetorheological fluid is the operating liquid which changes its behaviour with external stimulus by increasing the yield stress of fluid with the application of external magnetic field. Most of the vibration reducing equipment's is operated with single coil, and in this paper, study of multi coil magnetorheological damper is discussed and compared with the single coil for its magnetic flux density of the applied currents is studied by dividing equal and unequal number of turns of the coil in multi coil unlike in single coil damper.